PENGARUH PROMOSI FACEBOOK, TWITTER, DAN INSTAGRAM TERHADAP KEPUTUSAN WISATAWAN KE PANTAI PANDAWA BALI - Raditya, Topan; Suardana, I Wayan; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
This research intended to find out: (1) How is the influence of promotion on social media facebook, twitter and instagram on the image of the Pandawa beach?, (2) How does the promotion on social media Facebook, Twitter and Instagram influence the decision to visit tourists to the Pandawa beach? (3) What is the effect of the image of the Pandawa beach in touristic decisions?, The results showed (1) Social Media Promotion variable (X) has a direct influence on the Image (Y1) because it has a probability value (0,554) ? 0.05 which means there is a significant positive effect, (2) Social Media Promotion variable ( X) has a positive influence on Visiting Decision (Y2) because it has a probability value (0,207) ? 0.05 which means there is a significant positive effect. (3) Image variable (Y1) has a positive influence on Visiting Decision (Y2) because it has probability value (0,516) ? 0.05 which means there is a significant positive effect. Based on the conclusions stated above, several suggestions were given and were expected to provide benefits to the aid providers of the management of the Bali Pandawa beach. It is expected that the management to always maintain and try to improve the positive image of the Pandawa beach that has been embedded in the minds of the public and it is also hoped that the management will more aggressively promote tourist attractions on the Pandawa beach through social media, because promotion through social media is believed to be the most effective way to introduce beauty and the uniqueness of the Pandawa beach to the wider community.